Professor Samuelson on Operationalism in Economic Theory: Comment - Samuelson, Paul A. (Quarterly Journal of Economics, 1955)
Journal Article Professor Samuelson on Operationalism in Economic Theory: Comment Get access Paul A. Samuelson Paul A. Samuelson Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 2, May 1955, Pages 310–314, https://doi.org/10.2307/1882156 Published: 01 May 1955